Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xu, Xin; Wang, Jiahui; Tang, Yiming; Cui, Xuedan; Hou, Daibing; Jia, Hongjun; Wang, Shaobo; Guo, Lin; Wang, Jinhang; Lin, Aijun (Chemosphere (Oxford), 2023)
Titanium gypsum and biochar are considered effective amendments for mitigating soil salinity stress. However, the knowledge is inadequate regarding their efficiency and application as an improvement. In this study, TG-B composite was prepared by using industrial by-products titanium gypsum and biochar as raw materials and then modified by ball milling method, to characterize its microscopic characteristics and explore the improvement effect on saline-alkali soil and plant growth. Besides, we explored the mechanism of TG-B in improving saline-alkali soil and the dynamic balance of the solution reaction process. Our results showed that the CaSO4·2H2O particles in TG-B were finer, dispersed evenly, and contacted fully with soil gelatinous particles, which was more conducive to the improvement of saline-alkali soil. The results of TG-B with different ball milling ratios and different materials dosages indicated that the application rate of TG-B was 5%, and the optimum ratio of TG-B was TG: B (mass ratio) = 10:1, with the best soil improvement effect. The pot experiment proved that the indicators of indicating soil salinity such as pH, EC, SAR, and soluble Na+ decreased by 20.74%, 77.24%, 68.77%, and 44.70%, respectively, thus playing a good role in improving saline-alkali soil. In addition, pot experiments demonstrated that compared with the control group, the soil porosity and soil moisture content in the TG-B group increased by 15.95% and 38.71%, respectively, and further improve the structure and diversity of soil bacterial community when compared with titanium gypsum and biochar alone. Finally, the application of TG-B promoted the germination and growth of rice significantly through the synergistic effects of composite material components. These results all suggested that the application of TG-B was an effective strategy to improve soil salinity and promote plant growth. Therefore, it might provide new insights into the utilization of solid waste resources to improve saline-alkali lands. [Display omitted] •Titanium gypsum and biochar composites improved the effect of amendments on saline-alkali soils.•Titanium gypsum and biochar composites enhanced the physicochemical and biological properties of saline-alkali soils significantly.•The application of titanium gypsum and biochar composites mitigated the damage of salinity to rice.•Titanium gypsum and biochar had synergistic effects on saline-alkali land improvement.